The Third, Fifth and Sixth Painlevé Equations on Weighted Projective Spaces - Chiba, H. (Symmetry, Integrability and Geometry: Methods and Applications, 2016)
The third, fifth and sixth Painlevé equations are studied by means of the weighted projective spaces CP³(p,q,r,s) with suitable weights (p,q,r,s) determined by the Newton polyhedrons of the equations. Singular normal forms of the equations, symplectic atlases of the spaces of initial conditions, Riccati solutions and Boutroux's coordinates are systematically studied in a unified way with the aid of the orbifold structure of CP³(p,q,r,s) and dynamical systems theory.